Women and Sciences Health UNMSM 1930-1956 - Maldonado Félix, Héctor (2012)
The study of women as professional health sciences between 1930 and 1950 allows us to understand the process of modernization in Peru. In these decades the UNMSM was the main university, the professions were offered medicine, dentistry, pharmacy and obstetrics. The students of pharmacy and biochemist, faculty in 1943, were predominantly female. In the work environment of the 1940s and 1950s these woman were able to work independently and began working at the university and be known scientific authors. This autonomy is not a change to the traditional role but his claim.